Monitoring Suhu Air Akuarium untuk Ikan Hias berbasis Internet of Things - Iwan Fitrianto Rahmad; Adil Setiawan; Robby Ardyanto Marsudi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of technology that can be utilized from an internet connection is often also called IoT. IoT is a concept where there is interaction between humans and devices with the internet as a connecting medium, which can simplify human life. An example is being able to access electronic equipment such as an aquarium application to regulate the temperature online via Android. This can make it easier for ornamental fish keepers to no longer feel anxious about their pet fish. This system has the ability to control the temperature of the water in the aquarium to keep it normal. The results of the sensor data acquisition process will then be processed with fuzzy artificial intelligence embedded in a microcontroller chip. In this system, the coolant will turn on automatically when it reaches a certain temperature. And when the temperature reaches the normal category, the cooler will turn off